Assessment of targeted therapy opportunities in sinonasal cancers using patient-derived functional tumor models - Noora Lehtinen; Janne Suhonen; Kiesha Rice; Eetu Välimäki; Mervi Toriseva; Johannes Routila; Perttu Halme; Melissa Rahi; Heikki Irjala; Ilmo Leivo; Markku Kallajoki; Matthias Nees; et al. (Translational Oncology, 2024)
Malignant tumors derived from the epithelium lining the nasal cavity region are termed sinonasal cancers, a highly heterogeneous group of rare tumors accounting for 3 – 5 % of all head and neck cancers. Progress with next-generation molecular profiling has improved our understanding of the complexity of sinonasal cancers and resulted in the identification of an increasing number of distinct tumor entities. Despite these significant developments, the treatment of sinonasal cancers has hardly evolved since the 1980s, and an advanced sinonasal cancer presents a poor prognosis as targeted therapies are usually not available. To gain insights into potential targeted therapeutic opportunities, we performed a multiomics profiling of patient-derived functional tumor models to identify molecular characteristics associated with pharmacological responses in the different subtypes of sinonasal cancer. Methods: Patient-derived ex vivo tumor models representing four distinct sinonasal cancer subtypes: sinonasal intestinal-type adenocarcinoma, sinonasal neuroendocrine carcinoma, sinonasal undifferentiated carcinoma and SMARCB1 deficient sinonasal carcinoma were included in the analyses. Results of functional drug screens of 160 anti-cancer therapies were integrated with gene panel sequencing and histological analyses of the tumor tissues and the ex vivo cell cultures to establish associations between drug sensitivity and molecular characteristics including driver mutations. Results: The different sinonasal cancer subtypes display considerable differential drug sensitivity. Underlying the drug sensitivity profiles, each subtype was associated with unique molecular features. The therapeutic vulnerabilities correlating with specific genomic background were extended and validated with in silico analyses of cancer cell lines representing different human cancers and with reported case studies of sinonasal cancers treated with targeted therapies. Conclusion: The results demonstrate the importance of understanding the differential biology and the molecular features associated with the different subtypes of sinonasal cancers. Patient-derived ex vivo tumor models can be a powerful tool for investigating these rare cancers and prioritizing targeted therapeutic strategies for future clinical development and personalized medicine.